Conformational selection and dynamic adaptation upon linker histone binding to the nucleosome - Öztürk, Mehmet Ali; Pachov, Georgi V.; Wade, Rebecca C.; Cojocaru, Vlad (Nucleic acids research, 2016)
Abstract. Linker histones are essential for DNA compaction in chromatin. They bind to nucleosomes in a 1:1 ratio forming chromatosomes. Alternative configurati
Gesehen am 19.10.2020